Between Poets and Philologists: The Proposition of a Language Ideal in Apollonius Dyscolus’ Perì syntáxeos (Nuntius Antiquus, 2020)
Well known in the grammatical tradition as the formulator of the first treatise about the construction or syntax of the Greek language, Apollonius Dyscolus (2nd c. AD) devotes his Περὶ συντάχεως to a thorough examination of the Greek language, focusing mainly on its logical organization. However, the extensive reading of Apollonius’ work under this key has contributed to the overshadowing of the ‘philological’ dimension of this treatise perceived in the numerous analyses of constructions derived from poetic use, as well as in the quotations and allusions to poets and philologists within his work. Considering that the justification by Apollonius in his prologue was the “understanding of the writers and poets”, we ask ourselves: what role do poets and prose writers play in this study? We intend to show that Apollonius, despite never abandoning entirely the logic framework of his syntactic theory, puts in evidence a close reading of the Alexandrian philological tradition, both in the examples, quotations and allusions of poets and philologists, and in the procedure of analysis of Homer passages.